OPTIMALISASI WAKAF BERBASIS AGRIBISNIS DI LINGKUNGAN PONDOK PESANTREN SEBAGAI UPAYA MENUJU KEMADIRIAN EKONOMI UMAT (STUDI KASUS PONDOK PESANTREN SE-JAWA TIMUR) - Ahmad Husin (Jurnal Manajemen Dakwah, 2020)
Pondok Pesantren is an institution that is attached and becomes an inseparable part of the social system of Islamic society in Indonesia. The social role that is owned by pesantren until now continues to survive and still contributes a lot in people's lives. The resources owned by pesantren are very strong social capital to carry out its role as an institution that is tasked and responsible for forming a civil society in accordance with Islamic law. Religious institutions such as pesantren, as well as other non-governmental organizations, are potential institutions that so far have not played a direct role in the development of agriculture or agribusiness in rural areas. This study aims to create a model for optimizing the role of pesantren through empowering students and the community by prioritizing the potential of waqf-based agribusiness in East Java as a leading sector. This study uses a qualitative descriptive method with interpretation of observations. The collection method uses observation and literature study techniques. The result of this research is a synergy model for optimizing the role of Islamic boarding schools in community empowerment through sharia economics as a solution to achieve economic independence. Keywords: Islamic Boarding School, Agribusiness, Waqf, Sharia Contract